Application of Artificial Intelligence Technology in Oncology: Towards the Establishment of Precision Medicine - Hamamoto, Ryuji; Suvarna, Kruthi; Yamada, Masayoshi; Kobayashi, Kazuma; Shinkai, Norio; Miyake, Mototaka; Takahashi, Masamichi; Jinnai, Shunichi; Shimoyama, Ryo; Sakai, Akira; Takasawa, Ken; Bolatkan, Amina; et al. (Cancers, 2020)
In recent years, advances in artificial intelligence (AI) technology have led to the rapid clinical implementation of devices with AI technology in the medical field. More than 60 AI-equipped medical devices have already been approved by the Food and Drug Administration (FDA) in the United States, and the active introduction of AI technology is considered to be an inevitable trend in the future of medicine. In the field of oncology, clinical applications of medical devices using AI technology are already underway, mainly in radiology, and AI technology is expected to be positioned as an important core technology. In particular, “precision medicine,” a medical treatment that selects the most appropriate treatment for each patient based on a vast amount of medical data such as genome information, has become a worldwide trend; AI technology is expected to be utilized in the process of extracting truly useful information from a large amount of medical data and applying it to diagnosis and treatment. In this review, we would like to introduce the history of AI technology and the current state of medical AI, especially in the oncology field, as well as discuss the possibilities and challenges of AI technology in the medical field.